Canosa di Puglia, Italien. Die Architektur des Tempels von San Leucio. Die Arbeiten des Jahres 2017 - Wolf, Markus (e-Forschungsberichte des DAI, 2018)
At Canosa in Northern Apulia, the ancient Daunia, the Hellenistic temple under the early Christian church of San Leucio was explored. Based on the study of the foundations and the preserved architectural elements the temple could be reconstructed with Ionic columns in the front and rear of a middle building with Corinthian half-columns and telamons between them, crowned by a Doric frieze. The middle building surrounded the interior with a central square cella. A clear parallel for the telamons between half-columns and the pseudodipteral plan is the Olympieion of Agrigentum. Therefore we can consider a strong Greek influence from the Western Greek colonies, whereas the mix of the orders and the use of the Corinthian order outside are characteristic for late Hellenistic architecture.